2017
DOI: 10.1017/s0007114517003233
|View full text |Cite
|
Sign up to set email alerts
|

The effects of gelled konjac glucomannan fibre on appetite and energy intake in healthy individuals: a randomised cross-over trial

Abstract: Konjac glucomannan (KGM) is a viscous dietary fibre that can form a solid, low-energy gel when hydrated and is commonly consumed in a noodle form (KGM-gel). Increased meal viscosity from gel-forming fibres have been associated with prolonged satiety, but no studies to date have evaluated this effect with KGM-gel. Thus, our objective was to evaluate subsequent food intake and satiety of KGM-gel noodles when replacing a high-carbohydrate preload, in a dose-response manner. Utilising a randomised, controlled, cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…Some authors have suggested that glucomannan ingestion could also increase the gastric emptying time [14–16]. This effect may be related to the increased feeling of satiety reported in some studies [17]. The European Food and Safety Authority (EFSA) in 2010 reported a scientific opinion supporting the anti-cholesterol and weight reduction claims for glucomannan-containing drugs [18].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have suggested that glucomannan ingestion could also increase the gastric emptying time [14–16]. This effect may be related to the increased feeling of satiety reported in some studies [17]. The European Food and Safety Authority (EFSA) in 2010 reported a scientific opinion supporting the anti-cholesterol and weight reduction claims for glucomannan-containing drugs [18].…”
Section: Introductionmentioning
confidence: 99%
“…Fifty-nine percent of the included studies (n 17) compared the SQ response to meals of different composition. Of these seventeen studies, two used liquid meals (28,33) , fourteen solid meals (6,14,15,18,19,21,22,25,27,30,(34)(35)(36)(37)40) and one study compared solid v liquid meals (32) . Of these studies, three examined the effect of meals differing in energy content (14,28,33) and five studies compared the effect of meals differing in macronutrient composition (6,15,18,19,25) .…”
Section: Methodsmentioning
confidence: 99%
“…Of the thirty-three acute studies, twenty-nine were conducted in adults (6)(7)(8)11,(13)(14)(15)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)40,43) and four in adolescents (38,39,41,42) .…”
Section: Acute Studiesmentioning
confidence: 99%
“…Energy contributions from simple sugars and starch-rich foods should be reduced by replacing them with dietary fibre from natural or synthetic sources [ 51 ]. The main types of fibre used in order to reduce the energy density of carbohydrate-rich foods and produce greater weight loss are polydextrose, resistant starch, inulin, oligofructose, β-glucan and glucomannan [ 75 , 76 ]. Polydextrose is a soluble fibre used widely in the food industry that is fermented partially in the colon, and almost 60% of this fibre is excreted.…”
Section: Dietary Fibrementioning
confidence: 99%